Study the Prevalence of Colon Cancer - Sajad Abu Sharif Jadaan Odeh; Alaa Ali Jalil Ghamis; Namariq Ibrahim Khalaf Saleh; Tabarak Salem Bakhit Mandour; Fida al-Din Naseer Kamel Hameed; Ali Rahim Muheisen Hussein (Genius Journals, 2024)
The enzymes included in the oxidative protection system of the technological cycle of processing white and red grape varieties have been studied. It has been established that some technological operations predetermine an increase in oxidative stress. When processing red grapes, bound forms of SO2 increase, which reduces its antioxidant properties. Sulfation of red wort in the amount specified in the technological instructions is clearly not enough to provide antioxidant protection Colon cancer is a common preventable cancer. With the adoption of widespread colon cancer screening in the developed countries, the incidence and mortality of colon cancer have decreased in the targeted population
Keywords: Colon; Cancer; screening colonoscopy